PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABLE MEDIASI: STUDI PADA Hotel The Breezes Bali - I Putu Gede Angga Sugiarsa (Journal of Applied Management Studies, 2020)
This study discusses the role of service quality in increasing customer satisfaction and loyalty of The Breezes Bali. Responded in this study as many as 91 respondents by staying at The Breezes Bali hotel more than doubled, a minimum visit of 17 years. Determination of the sample using purposive sampling method. This study uses Partial Least Square (PLS) analysis with the SmartPLS program. The results of the study show that: 1) Quality of service is positive and significant to customer satisfaction 2) Quality of service is positive but not significant to customer loyalty 3) Positive and significant satisfaction of customer loyalty 4 ) Consumer satisfaction (customer satisfaction) Being able to be a mediating variable shown by the results of customer loyalty analysis can increase customer satisfaction and customer satisfaction can affect loyalty. The results of this study have implications for management policies by serving guests or customers well. Increased customer satisfaction is more emphasis on improving the company's image by praising the Good Hotel Breezes Bali. Continuing customer loyalty can be done by increasing word of mouth communication to customers. With word of mouth communication, customers will provide positive information about the Bali Wind Hotel to others.Keywords: service quality, satisfaction, customer loyalty.